Understanding the Root of Attack in Android Malware - Romli, Rahiwan Nazar; Zolkipli, Mohamad Fadli; Al-Ma'arif, Ahmad; Ramli, Muhamad Ramiza; Salamat, Mohamad Aizi (International Journal of Integrated Engineering, 2018)
With the rapid technology of mobile device and fast development of Android versions, Android malware has emerged and become a focus in current research. Security and privacy became the main issues in android malware. Therefore, it is essential to understand the behavior of Android malware in order to conceive an effective technique in malware detection and analysis. This article presents a comprehensive study regarding Android platform, its feature in android malware code and also discusses the result from previous study in order to support forward-looking in Android study.